CD155 in tumor progression and targeted therapy. (1st October 2022) - Zhan, Meixiao; Zhang, Zhiren; Zhao, Xiaoguang; Zhang, Yuncong; Liu, Tianqing; Lu, Ligong; Li, Xian-Yang
Abstract: CD155, also known as the poliovirus receptor (PVR), has received considerable attention in recent years because of its intrinsic and extrinsic roles in tumor progression. Although barely expressed in host cells, CD155 is upregulated in tumor-infiltrating myeloid cells. High expression of CD155 in tumor cells across multiple cancer types is common and associated with poor patient outcomes. The intrinsic functions of CD155 in tumor cells promote tumor progression and metastasis, whereas its extrinsic immunoregulatory functions in the tumor microenvironment (TME) involve interaction with the upregulated inhibitory immune cell receptor and checkpoint TIGIT, suggesting that CD155 and CD155 pathways are promising tumor immunotherapy targets. Preclinical studies demonstrate that targeting CD155 and its receptor (anti-TIGIT) using a single treatment or in combination with anti-PD-1 can improve immune-mediated tumor control. However, there is still a limited understanding of CD155 and its associated targeting strategies, especially antibody and immune cell editing-related strategies of CD155 in cancer. Here, we review the role of CD155 in host and tumor cells in controlling tumor progression and discuss the potential of targeting CD155 for tumor therapy.